CUTTING-EDGE LASER TECHNOLOGIES FOR EXPEDITED MEDICAL DIAGNOSTICS AND TREATMENT (Ustozlar uchun, 2026)
The use of advanced laser technology for fast medical diagnosis and treatment is gaining prominence in medicine and dentistry, facilitated by innovative software solutions for Raman and fluorescence analysis.The use of broadband, high-energy laser radiation fulfils two functions: firstly, as a therapeutic instrument [1, 2, 3, 4]; and secondly, as a means to augment the Raman luminescent diagnostic potential of a biological specimen [5] (specifically, in the context of biophotometry).